Surpassing the love of men: Romantic friendship and love between women from the renaissance to the present. - Faderman, Lillian (W Morrow, 1981)
A classic of its kind, this fascinating cultural history draws on everything from private correspondence to pornography to explore five hundred years of friendship and love between women.Surpassing the Love of Men throws a new light on shifting theories of female sexuality and the changing status of women over the centuries.
Keywords: amitié; amour; approches et analyses; corps; droits des femmes*; histoire et politique; hétérosexisme; patriarcat; personnes lesbiennes; phallocratie; ressource en ligne; sexualité; systèmes d'oppressions; thématiques